Multi-Locus Sequencing Reveals Putative Novel Anaplasmataceae Agents, ‘Candidatus Ehrlichia dumleri’ and Anaplasma sp., in Ring-Tailed Coatis (Carnivora: Nasua nasua) from Urban Forested Fragments at Midwestern Brazil - Perles, Lívia [UNESP]; Herrera, Heitor M.; Barreto, Wanessa T. G.; de Macedo, Gabriel C.; Calchi, Ana C. [UNESP]; Machado, Rosangela Z. [UNESP]; André, Marcos R. [UNESP] (MDPI, 2022)
The Anaplasmataceae family encompasses obligate intracellular α-proteobacteria of human and veterinary medicine importance. This study performed multi-locus sequencing to characterize Ehrlichia and Anaplasma in coati’s blood samples in Midwestern Brazil. Twenty-five samples (25/165—15.1%) were positive in the screening PCR based on the dsb gene of Ehrlichia spp. and were characterized using 16S rRNA, sodB, groEL, and gltA genes and the 23S-5S intergenic space region (ITS). Phylogenetic analyses based on all six molecular markers positioned the sequences into a new clade, with a common origin of Ehrlichia ruminantium. Haplotype analyses of 16S RNA sequences revealed the presence of two distinct Ehrlichia genotypes. Six samples (6/165, 3.6%) were positive in the screening nPCR for the 16S rRNA gene of Anaplasma spp. and were submitted to an additional PCR targeting the ITS for molecular characterization. Phylogenetic analyses based on both 16S rRNA gene and ITS positioned the Anaplasma sp. detected in the present study in a large clade with other Anaplasma sp. previously detected in ticks and wild animals and in a clade with ‘Candidatus Anaplasma brasiliensis’, respectively. Based on distinct molecular markers, the present work described a putative novel Anaplasmataceae agent, namely ‘Candidatus Ehrlichia dumleri’, and Anaplasma sp. closely related to the previously described ‘Candidatus Anaplasma brasiliensis’.
Keywords: Procyonidae; Rickettsiales; tick-borne agents; wild animals